2021
DOI: 10.5114/hivar.2021.109249
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to anti-retroviral therapy during COVID-19 pandemic among adolescents born HIV-positive

Abstract: Successful rollout of anti-retroviral therapy (ART) in Africa has resulted in a steep decline in HIV incidence. Even though this has been a long-awaited development, it is not the case for adolescents (10-19 years) born HIV-positive. Given this brief background and dangers imposed by COVID-19 pandemic, adolescents born HIV-positive are at great risk. A systematic review was conducted and reported, according to preferred reporting items for meta-analyses (PRISMA). Studies were drawn from database search perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Economic barriers are often interrelated with other biopsychosocial barriers and pose a barrier to optimal adherence among adolescents with HIV (Hlophe et al 2023 ; Kansiime et al 2021 ). A systematic review of studies in South Africa found that food insecurity is common in most low-socioeconomic settings in South Africa and poses a barrier to adolescents taking their ART medication as prescribed (Muchena & Kalenga 2021 ). Ahmed et al ( 2023 ) found that COVID-19 lockdowns, service restrictions and adjustments increased food insecurity and poverty in many communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic barriers are often interrelated with other biopsychosocial barriers and pose a barrier to optimal adherence among adolescents with HIV (Hlophe et al 2023 ; Kansiime et al 2021 ). A systematic review of studies in South Africa found that food insecurity is common in most low-socioeconomic settings in South Africa and poses a barrier to adolescents taking their ART medication as prescribed (Muchena & Kalenga 2021 ). Ahmed et al ( 2023 ) found that COVID-19 lockdowns, service restrictions and adjustments increased food insecurity and poverty in many communities.…”
Section: Discussionmentioning
confidence: 99%
“…A shortage in health workers meant that fewer healthcare workers were available to monitor adolescents living with HIV on ART and conduct follow-ups. The lack of HIV services also meant that adolescents living with HIV lost a support structure, which increased feelings of hopelessness and helplessness, and in turn decreased their motivation to stay adherent to HIV treatment during the pandemic (Muchena & Kalenga 2021 ). In addition, the national responses to curb the spread of COVID-19 disrupted the support services that adolescents received, further highlighting the structural challenges experienced by adolescents living with HIV (Van Wyk & Mayman 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation